Analysis of the Dynamical Behavior of Firms in a Three Layered Modular Assembly Model - LU, Jianjun; ., Wen Tian (Information Management and Business Review, 2012)
This paper formulate an option model considers supplier’s reaction as the profit sharing in module production, and analyses it by the agent theory. A dynamic environment in the model of the system of the production of modules of three layers is assumed, and the maker and the supplier are modeled by the technique of Genetic Programming (GP) as an agent who takes the action of selfoptimization. As result, the condition that the agent can exist continuously in the market is requested. In conclusion, violent competition and the selection of the similar agent are found even in the model of the option to consider the profit sharing and the reaction.